Pricing of alcohol in Canada: A comparison of provincial policies and harm‐reduction opportunities. (4th November 2015) - Giesbrecht, Norman; Wettlaufer, Ashley; Thomas, Gerald; Stockwell, Tim; Thompson, Kara; April, Nicole; Asbridge, Mark; Cukier, Samantha; Mann, Robert; McAllister, Janet; Murie, Andrew; Pauley, Chris; et al.
Abstract: Introduction and Aims: Alcohol pricing is an effective prevention policy. This paper compares the 10 Canadian provinces on three research‐based alcohol pricing policies—minimum pricing, pricing by alcohol content and maintaining prices relative to inflation. Design and Methods: The selection of these three policies was based on systematic reviews and seminal research papers. Provincial data for 2012 were obtained from Statistics Canada and relevant provincial ministries, subsequently sent to provincial authorities for verification, and then scored by team members. Results: All provinces, except for Alberta, have minimum prices for at least one beverage type sold in off‐premise outlets. All provinces, except for British Columbia and Quebec, have separate (and higher) minimum pricing for on‐premise establishments. Regarding pricing on alcohol content, western and central provinces typically scored higher than provinces in Eastern Canada. Generally, minimum prices were lower than the recommended $1.50 per standard drink for off‐premise outlets and $3.00 per standard drink in on‐premise venues. Seven of 10 provinces scored 60% or higher compared to the ideal on indexing prices to inflation. Prices for a representative basket of alcohol products in Ontario and Quebec have lagged significantly behind inflation since 2006. Discussion and Conclusions: While examples of evidence‐based alcohol pricing policies can be found in every jurisdiction in Canada, significant inter‐provincial variation leaves substantial unrealised potential for further reducing alcohol‐related harm and costs. This comparative assessment of alcohol price policies provides clear indications of how individual provinces could adjust their pricing policies and practices to improve public health and safety. [Giesbrecht N, Wettlaufer A, Thomas G, Stockwell T, Thompson K, April N, Asbridge M, Cukier S, Mann R, McAllister J, Murie A, Pauley C, Plamondon L, Vallance K. Pricing of alcohol in Canada: A comparison of provincial policies and harm‐reduction opportunities. Drug Alcohol Rev 2016;35:289–297]